Environmental, social, and governance performance in tax avoidance: Evidence from Indonesia’s mining and energy sector - Sri Astuti; Nur Diana; Kunti Sunaryo; Indah Kartika Sandy; Dhea Arsinta Yuliana; Heri Susanto (Universitas Islam Malang, 2026)
This study aims to analyze the relationship between Environmental, Social, and Governance (ESG) performance and tax avoidance of listed companies in the mining and energy sector in Indonesia, a topic that has been rarely explored in emerging economies, including in the extractive industries with high risk. To fill this gap, quantitative method is adopted through the use of the panel data of 32 publicly listed companies for the period 2018-2022. Multiple regression with a number of firm-level controls, such as firm size (SIZE), firm age (AGE), free cash flow (CASH), asset to income ratio (AIN), return on assets (ROA), leverage (LEV) and ownership concentration (TOP) and the tax avoidance proxy effective tax rate (ETR) is employed. The findings show that ESG performance is strongly related with ETR, where the higher ESG scores the company, the lower the ETR. Among the control variables, ROA, CASH, AIN, AGE and TOP have significant effects on tax outcomes while SIZE and LEV show no significant effects. This result likely shows how industry-specific factors shape financing decisions, especially given how similar mining and energy firms tend to be. Also, firms with higher ESG scores tend to have a more robust internal system and more resources, which could enable them to better manage their tax strategy in a way that is within legal boundaries and keeps stakeholders trust.